Organizational resources and product innovation performance: the moderating role of government support / Malvern Abdullah - Abdullah, Malvern (2011)
There had been numerous studies on the determinants of firm’s product innovation performance. The most common question that has attracted much attention among scholars and practitioners is the reason as to why some firms perform better while the others do not. To investigate further, this thesis is conducted by focusing on several key organizational resources that affect product innovation performance. Drawing on Resource Based View (RBV) theory, this study examines the internal organizational resources that are intangible, in which found to influence the film’s product innovation performance. This study explores the relationships among these firm’s resources and product innovation performance within the electrical and electronic manufacturer in Malaysia. A model framework is also proposed. Altogether fifteen hypotheses emanating from the framework are presented The study utilized mail survey of questionnaires as primary mean to obtain information for the study. Prior to the development of survey instrument, several ministries. government. agencies, and manufacturers within the electrical and demonic industry in Malaysia were interviewed to obtained additional information for inclusion into the research. The findings of this study are based on the responses obtained from sixty one manufacturing firms in Malaysia. The results indicated that the imam-mil organizational resources of product innovation experience, firm’s reputation, product innovation collaboration, and knowledge management orientation all have some impact on product innovation performance. However, the main objective of the study is to analyze the combined effect of these resources on product innovation performance. The results showed that collectively, product innovation collaboration was found to affect product innovation performance the most, followed by firm’s reputation. The research found that product innovation experience and knowledge management orientation lost their predictive power to affect product innovation performance with the presence of all other organizational resources under study. Additionally, government support was also found to moderate the relationship between organizational resources and product innovation performance. Specifically, firm’s product innovation performance improves as more government supports are received. The implications of these findings for research and practice are discussed and the limitations of the study were also presented. Finally, the directions for future research were also suggested.